The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8198126
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Temperatures and Kinetic Freeze-Out Volume on Centrality in Au-Au and Pb-Pb Collisions at High Energy

Abstract: Centrality-dependent double-differential transverse momentum spectra of negatively charged particles (π−, K−, and p¯) at the mid(pseudo)rapidity interval in nuclear collisions are analyzed by the standard distribution in terms of multicomponent. The experimental data measured in gold-gold (Au-Au) collisions by the PHENIX Collaboration at the Relativistic Heavy Ion Collider (RHIC) and in lead-lead (Pb-Pb) collisions by the ALICE Collaboration at the Large Hadron Collider (LHC) are studied. The effective tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 63 publications
5
31
1
Order By: Relevance
“…However, the collisions become less violent as the centrality decreases and less number of participants involve in the interactions which results in comparatively low kinetic freezeout temperature. This is in agreement with[11][12][13][14][15][16], but in disagreement with[17][18][19][20].…”
supporting
confidence: 81%
“…However, the collisions become less violent as the centrality decreases and less number of participants involve in the interactions which results in comparatively low kinetic freezeout temperature. This is in agreement with[11][12][13][14][15][16], but in disagreement with[17][18][19][20].…”
supporting
confidence: 81%
“…The non-strange particles have a larger production cross-section than the strange or multi-strange particles; therefore, the non-strange particles freezeout later than the strange (multi-strange) particles. This result is consistent with that of our recent work [ 10 ]; however, in [ 10 ], the authors also observed a separate decoupling of strange and multi-strange particles. It is noteworthy that the observed at the RHIC is lower than that of the LHC.…”
Section: Resultssupporting
confidence: 93%
“…It is very important to search for the correct trend of with energy and centrality. Furthermore, there are different kinetic freezeout scenarios found in the literature, which include single, double, triple and multiple kinetic freezeout scenarios [ 5 , 6 , 7 , 8 , 9 , 10 ]. In the single kinetic freezeout scenario, one set of parameters is used for the strange, multi-strange and non-strange particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-energy collisions, there are two types of particle production process: (1) soft process ad (2) hard process. For soft process, there are various methods which include but are not limited to blast wave model with boltzmann Gibbs statistics [5][6][7], blast wave model with Tsallis statistics [8][9][10], Hage-dorn thermal model [20], and standard distribution [33,34]. We are interested in the blast wave model with Tsallis statistics.…”
Section: The Methods and Formalismmentioning
confidence: 99%